Early feeding practices and their determinants: national food, nutrition and physical activity survey 2015-2016 - Silva,Sara (2019)
Introduction: Feeding practices in the first two years of life influence the childs growth and future health. Updated information on factors associated with breastfeeding and complementary feeding practices is needed to support maternal and child health policies. Objectives: To describe breastfeeding and complementary feeding practices and associated factors on a representative sample of Portuguese children. Methodology: The study includes a sample of 904 children from 3 to 35 months from the National Food, Nutrition and Physical Activity Survey (IAN-AF 2015-2016). A questionnaire about feeding practices during the first years of life was applied to parents/caregivers. Survival analysis was used to estimate proportions and a Cox regressions hazard model was used to estimate associations. Results: The proportion of children never breastfed was around 6% and 30% stopped breastfeeding before 4 months. The breastfeeding duration was longer in older, less educated and unemployed mothers. Only 3.3% of infants started complementary feeding before 4 months. Weaning started with a vegetable soup in 66% of infants. Around 7% of children drunk cow milk before completion of 12 months of age and the risk of early consumption was increased in infants from less educated and unemployed mothers. Children assisted by a primary health care physician had a higher risk of early introduction of cow milk in comparison with the paediatrician. Conclusions: Among Portuguese children, early feeding practices seem to be globally according to recommendations. An early stop of breastfeeding is more frequent in higher educated women and active workers. Other practices that could compromise childrens growth such as the early introduction of cow milk is more frequent in socio-economic disadvantaged families.